Teoría lingüística y evaluación de la competencia gramatical en sujetos con trastornos profundos del desarrollo. - Anula Rebollo, A. (Didáctica. Lengua y Literatura, 1997)
The ami of this work is to apply a numnber of gramtnatical criteria concerning verbal lexical knowledge to the dcsign of experimental tasks for the purpose of assessing linguistic competence. Gur major concern is to show that La presente investigación ha sido pamci al mente subvencionada por la D.C J.C YE, proyecto PS93-0032, y por tío proyecto tinanciado por el CIDE, dimigido por la segunda autora, Didcic¡ica. 9.39-66. Servicio de Publicaciones UCM. Madrid. 199? A ¡br' rio A utílc¿ Rc'bo Po j Mercedes Belo¡e/?on Cc¿nnonc, 40 grammatical theory can help clarify the comprehension difficulties shown hy people with Dowri syndrome and autism. We will also stress the implications of the results of empirical research for the educational imitervention of people with severe developmental disorders.
Keywords: G; -anmníatícal develop¡nent A ssessment tasks Lic guístic dejicits Developmental disorders Doven syndrome Au¡ism Educational mier